1 3 5 7 9 1 1 1 3 1 5 1 7 1 9 2 1 2 3 2 5 2 7 2 9 . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . **Find the sum of numbers in the 123rd row.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If n is even, the answer would be n(n^2+1)
Log in to reply
Wrong , think again.
Log in to reply
n^3+n, this is what it is.
Log in to reply
@Mehul Arora – Wrong.Think again
Log in to reply
@Nihar Mahajan – -_- you think again.
Log in to reply
@Mehul Arora – Its still n 3 . Now think again -_-
Note: People who see these comments , please don't think that we are fighting. Thats our unique way of talking.
Log in to reply
@Nihar Mahajan – I'm assuming what you meant by 'n' is the row number, while what Mehul meant by 'n' is the pattern (even numbers instead of odd).
Log in to reply
@Vishnu Bhagyanath – Yes. Absolutely! That was what I thought!
Here's a stronger result (covers all positive integral values of n ):
Consider the arithmetic progression ( a k ) k = 1 ∞ given by a k = 2 k − 1 . All the successive elements of the triangle follow this AP.
Now, consider the n th row of the triangle. It can be observed that the sum we need is the sum of elements of ( a k ) from k = ( T n − 1 + 1 ) to k = T n where T x is the x th triangular number . Denote our sum of the elements of the n th row as S n . Then,
S n = k = T n − 1 + 1 ∑ T n a k
Since ( a k ) is an AP sequence and we know that T x − T x − 1 = x (obviously), we use the summation formulas of AP. We get,
S n = 2 T n − ( T n − 1 + 1 ) + 1 ( a T n − 1 + 1 + a T n ) ⟹ S n = 2 n ( 2 ( T n − 1 + 1 ) + 2 ( T n ) − 2 ) ⟹ S n = 2 n ( 2 ( T n + T n − 1 ) ) = n ( 2 T n − 1 + n ) ⟹ S n = n ( ( n − 1 ) n + n ) = n ( n ( n − 1 + 1 ) ) ⟹ S n = n ⋅ n ⋅ n = n 3
∴ S n = n 3 ∀ n ∈ Z +
Note / Clarification: By definition, we have T 0 = 0 .
Log in to reply
Nice work! BTW did you try my 1000 followers problem?
Your solutions are so elegant that anyone can recognize it's written by you even without seeing your name. I did . Great solution . 😀😀
Or we can simply continue from the quoted line as usual with simple sum formulas.
S n = k = T n − 1 + 1 ∑ T n a k = k = T n − 1 + 1 ∑ T n ( 2 k − 1 ) ⟹ S n = ( T n ) 2 − ( T n − 1 ) 2 = 4 1 ( n 2 ( n + 1 ) 2 − ( n − 1 ) 2 n 2 ) ⟹ S n = 4 1 n 2 ( ( n + 1 ) 2 − ( n − 1 ) 2 ) = 4 1 n 2 ( 4 ⋅ n ⋅ 1 ) = n 3
First row sums 1, that is 1^3. Second row sums 8, that is 2^3. Third row sums 27, that is 3^3. Fourth row sums 64, that is 4^3. So, 123rd row sums 123^3 = 1860867
Notice that:
3 + 5 = 8 = 2 3 the sum of elements in the 2 n d row.
7 + 9 + 1 1 = 2 7 = 3 3 the sum of numbers in the 3 r d row.
1 3 + 1 5 + 1 7 + 1 9 = 6 4 = 4 3 the sum of numbers in the 4 t h row.
2 1 + 2 3 + 2 5 + 2 7 + 2 9 = 1 2 5 = 5 3 the sum of numbers in the 5 t h row.
Thus, the sum of numbers in the 1 2 3 r d row is 1 2 3 3 = 1 8 6 0 8 6 7 .
Problem Loading...
Note Loading...
Set Loading...
Consider the n t h row and let t 1 ( n ) , t n ( n ) denote its 1st and last term respectively. By observation we have the relation :
2 t 1 ( n ) + t n ( n ) = n 2
Since in this problem , n is odd and the n t h row is an arithmetic progression , we have n 2 as the middle term and thus the sum of terms of n t h row is given by :
n × ( m i d d l e t e r m ) = n ( n 2 ) = n 3
So required answer is 1 2 3 3 = 1 8 6 0 8 6 7 .
Bonus: What if n is even?